Kritik al-Ghazali terhadap Kekekalan Alam - Sahidi Mustafa (Universitas Darussalam Gontor, 2015)
The concept of the creation of universe offered by Neo-Platonism philosopher such as al-Kindi, al-Farabi, and Ibnu Sina are philosophical concept existed and came as an early moment of development of Islamic philosophy interrelated to God, ultimately about his Existence and Characteristics. One of the topics is how God created the universe. According to al-Farabi and Ibnu Sina, God created this universe by way of emanation in order to prevent Himself from the new attitudes. Consequently, universe has eternal feature (qadim) as God as well, in the case of everything overflowed from qadim is also qadim. Al-Ghazali refuted this theory because it contradicted with al Qur’an’s thought which clearly explained that God created the entire universe. The universe should not qadim and it means that God existed in the first, and then created universe later as we know today. On the contrary, in the view of Muslim philosopher, the universe should be qadim because God created it from all eternity. For them, it is impossible that God existed by Himself without any creation before. God, according to them is impossible to be changed, so that is impossible as well if God changed from did not create yet before and then creates. Al-Ghazali persistently opposed the concept of eternity. Al Ghazali saw if this universe is qadim so it is impossible that universe created by God. The concept of qadim will led to the conclusion that universe born by itself, it was not created by God. This critique has been written by al-Ghazali in Tahafut al-Falasifah. This paper will present the concept of eternity which was discussed by al-Farabi and Ibn Sina and al Ghazali’s critique toward it as well.